2020
DOI: 10.1149/1945-7111/ab819c
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Support Microstructure Impact on High Current Density Transport Resistances in PEMFC Cathode

Abstract: Cell voltages at high current densities (HCD) of an operating proton-exchange membrane fuel cell (PEMFC) cathode suffer from losses due to the local-O2 and bulk-H+ transport resistances in the catalyst layer. Particularly, the microstructure of high surface area carbon (HSC) support upon which both the platinum catalyst and ionomer are dispersed play a pivotal role in controlling the reactant transport to the active site in the catalyst layer. In this study, we perform a systematic analysis of the underlying m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
212
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(213 citation statements)
references
References 47 publications
1
212
0
Order By: Relevance
“…More interestingly, this catalyst also demonstrates high power/performance compared with the state-of-the-art electrocatalysts, Pt(20 wt%)NPs/VC (JM), Pt(40 wt%)NPs/Hi-spec (JM), and Pt(50 wt%)NPs/HSAC (Tanaka), which is very important in reducing the size and cost of the fuel cell stack. [49] Last but not the least, it is worth noting that in this study, neither the amount of g-CN nor the macroporosity of the MPC support were optimized, thus it is likely that the electrocatalytic performance of g-CN@MPC-supported Pt NW catalysts can still be further increased. Furthermore, Pt metal and Pt alloys (e.g., Pt 3 Ni) with other morphologies (e.g., Nanoframe) which have demonstrated ultrahigh electrocatalytic activity toward the ORR [4,50] can be incorporated into g-CN@MPC to further enhance the electrocatalytic activity and electrochemical stability of this electrocatalyst approach.…”
Section: Resultsmentioning
confidence: 93%
“…More interestingly, this catalyst also demonstrates high power/performance compared with the state-of-the-art electrocatalysts, Pt(20 wt%)NPs/VC (JM), Pt(40 wt%)NPs/Hi-spec (JM), and Pt(50 wt%)NPs/HSAC (Tanaka), which is very important in reducing the size and cost of the fuel cell stack. [49] Last but not the least, it is worth noting that in this study, neither the amount of g-CN nor the macroporosity of the MPC support were optimized, thus it is likely that the electrocatalytic performance of g-CN@MPC-supported Pt NW catalysts can still be further increased. Furthermore, Pt metal and Pt alloys (e.g., Pt 3 Ni) with other morphologies (e.g., Nanoframe) which have demonstrated ultrahigh electrocatalytic activity toward the ORR [4,50] can be incorporated into g-CN@MPC to further enhance the electrocatalytic activity and electrochemical stability of this electrocatalyst approach.…”
Section: Resultsmentioning
confidence: 93%
“…GrC carbon support (MEA 1 and MEA 2) has almost no internal porosity, which results in a low total surface area, where all the Pt particles distribute on the surface of the support. For MEA 3, according to Nagappan et al, 26 high surface area carbon (HSC) support has around 3-5 times higher total surface area than Vulcan carbon support due to its high internal porosity. Figure 7a shows the effective ionic conductivities for MEA 1 and MEA 2 (properties defined in Table I).…”
Section: Resultsmentioning
confidence: 99%
“…At low RH, MEA 3 with the HSC support showed lower effective ionic conductivity. It was shown recently by Ramaswamy et al 26 that surface area of smaller meso-pores (> 8 nm) of the carbon support determines the continuity and uniformity of the ionomer distribution in the catalyst layer. The GrC carbon support in MEA 2 has less to no meso-pores compared to the HSC used in MEA 3, which results in a larger effective ionic conductivity of MEA 2.…”
Section: Resultsmentioning
confidence: 99%
“…However, this location ensures that the Pt surface is in contact with the ionomer, leading to adsorption of sulfonic acid groups and poisoning effects. 13,14 Based on such observations, Harzer et al 13 suggested that an ideal catalyst ought to have most of the Pt particles outside for good mass transport, while having a small fraction of internal Pt to increase total mass activity. Similar results have also been obtained by other researchers.…”
mentioning
confidence: 99%